Higher Protein Intake Does Not Potentiate Skeletal Muscle Vitamin D Receptor. (7th June 2021) - McKenna, Colleen; Salvador, Amadeo; Askow, Andrew; Paulussen, Kevin J.M.; Keeble, Alexander; Paluska, Scott; De Lisio, Michael; Khan, Naiman; Burd, Nicholas
Abstract: Objectives: The loss of muscle mass with age increases not only risk of functional impairment, but also development and exacerbation of cardiometabolic disease. While dietary protein intake and habitual resistance exercise are traditional strategies to offset age-related decrements in lean mass, it is important to define the role of other regulatory nutrients in this process. Dietary vitamin D (VD) has received particular interest as muscle vitamin D receptor (VDR) is associated with hypertrophy. Importantly, beyond being a significant source of high-quality protein, animal-based protein foods are also rich in VD. While previous efforts have investigated the provision of protein and/or VD supplements during a resistance training program, the influence of dietary protein composition and diet-derived VD on resistance exercise adaptations remains unknown. Methods: Forty-one middle-aged adults (mean ± SD: age 50 ± 8 y, BMI 27 ± 4 kg/m 2, M = 19, F = 22) were stratified and randomized to consume either high (1.68 ± 0.26 g/kg/d) or moderate (1.16 ± 0.19 g/kg/d) amounts of animal-based protein during a 10-week dietary counseling-controlled resistance training program. Dietary intake was monitored by biweekly 3d diet records (ASA24). Dual-energy x-ray absorptiometry and muscle biopsies were performed pre- and post-intervention. Total RNA was extracted and reverse-transcribed for muscle gene expression by quantitative polymerase chain reaction. Intervention outcomes and their relationships were analyzed using linear mixed effects models and repeated measures correlation, respectively, by R. Results: VDR gene expression increased regardless of condition ( P  = 0.007; 95% CI: 0.13, 0.84). Upregulation of VDR expression was correlated with gains in appendicular lean mass (r = 0.44; P  = 0.011; CI: 0.10, 0.68). While protein intake did not affect VDR expression, animal-based protein diet density (servings/1000 kcal) was modestly correlated with VDR expression (r = 0.42; P  = 0.014; CI: 0.08, 0.67). There was no relationship between dietary VD and VDR expression. Conclusions: Our results suggests that moderate dietary protein intake is sufficient to support resistance exercise-induced VDR upregulation and lean mass gain in middle-aged adults. Funding Sources: Funded in part by the Beef Checkoff. CFM funded by JBT Fellowship, UIUC.